(untitled) - Wilkens, Steve; (1955-...) (U.S.A, 2014)
Life confronts us with an endless stream of questions. Some are trivial. But some draw us into the deepest dimensions of human inquiry, a place where our decisions have profound implications for life and faith. Is there a God, and if so, how can I know anything about who or what God is? Is the quest for truth an elusive dream? How should I live and what should I value? What happens at the end of my biological existence? These questions lead people of every creed and belief to consider important existential concepts. But many people wrestle with the relationship between faith and reason as they dig into the roots of this theological and philosophical pursuit. Does a shared interest in a common set of questions indicate that philosophy and theology are close kin and allies, or are they competitors vying for our souls, each requiring a loyalty that excludes the other? In Faith and Reason, Steve Wilkens edits a debate between three different understandings of the relationship between faith and reason, between theology and philosophy. The first viewpoint, Faith and Philosophy in Tension, proposes faith and reason as hostile, exclusive opposites, each dangerous to the integrity of the other. The second, Faith Seeking Understanding, suggests that faithful Christians are called to make full use of their rational faculties to aid in the understanding and interpretation of what they believe by faith. In the third stance, Thomistic Synthesis, natural reason acts as a handmaiden to theology by actively pointing people toward salvation and deeper knowledge of spiritual truths. Bringing together multiple views on the relationship between faith, philosophy and reason, this introduction to a timeless quandary will help you navigate, with rigor and joy, one of the most significant discussions of the Christian community.
Keywords: Religion -- Christian Theology -- General